Comparative Presentation of the Sophistic Theory and the Theory of Social Constructionism - Golubović, Dejan Lj. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
Social constructionism is a postmodern view the essence of which includes an idea of truth conditioned by society and history and of truth constructed within a wide spectrum of social interactions. The consequences of this view are that no knowledge deserves a privileged ontological status and that we can only speak about different versions of truth. The aim of the paper is a critical reconsideration of the originality of these ideas. The starting point is the hypothesis that there is a significant degree of theoretical congruence between sophism and social constructionism, implying that social constructionism could be observed to a great extent as a revitalization of old sophist ideas interpreted in a formally new manner. The methodology is comparative and interpretative text analysis, while the units of analysis are reflexivity, agnosticism, anti-essentialism, relativism, and social construction of truth. The structure of the paper comprises two entireties—the first entirety defines the concepts of sophism and social constructionism, while the second one presents the key ideational overlaps between these two movements. The conclusion is that there is a high degree of congruence, but also a considerable disparity, between sophism and social constructionism. The congruence is present in the reflexive relation towards one’s own theoretical and methodological limitations, radical distrust in the epistemic capacities of the knower and relativistic conception of truth, while with regard to socially constructed truth, the congruence is absent. By this, the hypothesis set is largely confirmed, the epithet of an authentic sociological theory is attributed to social constructionism and the significance of a philosophical orientation with many elements of modernity is attached to sophism.
Keywords: social constructionism; sophism; anti-essentialism; agnosticism; relativism; social construction of the truth